Comparison of functional outcomes of modular bipolar hemiarthroplasty done in direct lateral versus posterior approaches - Bhaskaran, Navneeth Sushama; Ibrahim, Mohammed Manzoor Kuriyappulli; Sunny, Nevil; Raj, Ashwin (International Journal of Research in Orthopaedics, 2025)
Background: Fracture neck of femur (FNF) is a common osteoporotic injury in the elderly, contributing significantly to morbidity and mortality. Hemiarthroplasty is widely accepted for displaced FNF; however, the optimal surgical approach remains debated. This study compared the functional and radiological outcomes of cemented modular bipolar hemiarthroplasty performed via direct lateral versus posterior approaches. Methods: A retrospective cohort study was conducted at Kovai Medical Centre and Hospital, Coimbatore, including 100 patients (aged 51–90 years) who underwent cemented modular bipolar hemiarthroplasty for FNF between June 2018 and June 2019, with one-year follow-up. Patients were grouped based on surgical approach: direct lateral (Group L, n=50) and posterior (Group P, n=50). Intraoperative and postoperative parameters, including operative time, blood loss, hospital stay and complications, were recorded. Functional outcome was assessed using the Harris Hip Score (HHS) and radiological assessment included stem alignment, loosening, acetabular erosion and heterotopic ossification. Statistical analysis was performed using Chi-square and t-tests, with p<0.05 considered significant. Results: Baseline demographics and injury characteristics were comparable between groups. Group L had slightly higher mean operative time and blood loss, while hospital stay and time to weight bearing were similar. Functional outcomes favored Group L, with a higher mean HHS (84.04 vs. 80.06) and greater proportion of excellent/good results (90% vs. 68%). Radiological complications were infrequent and comparable across groups. Conclusions: Cemented modular bipolar hemiarthroplasty is effective in managing FNF in the elderly. The direct lateral approach offers superior functional outcomes, whereas the posterior approach provides shorter operative time but higher dislocation risk. Surgical approach should be individualized.